EVALUATION OF NUTRIENT POTENTIALS OF EFFLUENT FROM BIODIGESTION OF WATER WEED SPECIES AS SOIL AMMENDEMENT - Adanikin, B A; Adesanwo, O O; Ogunwande, G A (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
The study assessed the nutrient potential of water weeds effluent from biogas production as soil amendment.  Three species of water weeds [Duck weed (DW) (Lemna minor), morning glory (MG) (Ipomea asarifolia) and water hyacinth (WH) (Eichhornia crassipes)] were subjected to digestion in a batch type anaerobic digester. The water weeds were co-digested in a calculated mixture ratio (w/w dry Basis) of DW: WH (30:70, 50:50, 70:30, 100:0), MG: WH (30:70, 50:50, 70:30, 100:0) and WH (100%) and monitored for a retention period of 16 weeks.  The raw water weeds and effluents from bio-digestion were analysed for plant nutrients (N, P, K, Ca, Mg and OC) and heavy metals (Mn, Pb, Cr, Ni, and As) using standard methods. The result showed positive significant effect of anaerobic digestion of water weeds on nutrient content, for example, 4.76% N and 9.05% N were obtained from raw DW and bio -digested effluent respectively. Similar trend was noticed for micronutrients.  Significant reduction in heavy metal content was recorded after bio-digestion, Cd, Pb and Ni content in raw water weed were 1.62, 1.5 and 0.03 mg kg-1 respectively while 0.09, 0.080 and 0.015 mg kg-1 were obtained after bio-digestion. Among the different mixtures of water weeds, digestion of sole material gave higher values in major and minor nutrients compared with effluent from mixed water weeds. The study concluded that effluents from bio-digestion of water weeds are richer in plant nutrients than raw samples thus giving dual benefits: production of biogas and resulting effluent as fertilizer.